Application of sutureless technique in total anomalous pulmonary venous connection repair. Issue 11 (18th August 2022) - Wang, Zhangwei; Ding, Nan; Yi, Hanlu; Zhu, Yaobin; Li, Zhiqiang; Yan, Daole; Li, Xiaofeng; Bai, Song
Abstract: The sutureless technique was initially used for the treatment of postoperative pulmonary vein obstruction (PVO) in patients with total anomalous pulmonary venous connection (TAPVC). However, as the effectiveness of the sutureless technique has been confirmed and widely developed, the sutureless technique has been used for the primary treatment of high‐risk children with TAPVC who are at high risk of PVO. Compared with traditional surgery, the sutureless technique significantly reduces the incidence of postoperative PVO, re‐intervention rate due to PVO, and postoperative mortality, but there are potential complications such as pericardial and confluent venous anastomosis, phrenic nerve damage, air embolism. In addition, the sutureless technique is not effective in dealing with the progressive stenosis of the pulmonary veins after sutureless surgery and diffuse stenosis of extrapulmonary proximal veins and intrapulmonary veins. These make the efficacy and safety of this procedure controversial. This paper reviews the research status of the sutureless technique in TAPVC repair at home and abroad over the years.